Induction of neutralizing antibody responses by AAV5-based vaccine for respiratory syncytial virus in mice - Ma, Gangyuan; Xu, Zeping; Li, Chinyu; Zhou, Feng; Hu, Bobo; Guo, Junwei; Ke, Changwen; Chen, Liqing; Zhang, Guilin; Lau, Hungyan; Pan, Hudan; Chen, Xixin; et al. (Frontiers in Immunology, 2024)
Respiratory Syncytial Virus (RSV) is a significant cause of respiratory illnesses worldwide, particularly in infants and elderly individuals. Despite the burden RSV imposes, effective preventive measures are limited. In this study, we explored the potential application of a recombinant adeno-associated virus 5 (rAAV5) vector-based RSV vaccine, focusing on the expression of the pre-fusion (Pre-F) protein structure. Through intramuscular immunization in mice, the rAAV5-RSV-Fm vaccine demonstrated positive humoral and induced antibody titers against RSV strains A and B for up to 120 days post-immunization. Notably, intranasal administration also elicited protective antibodies. Characterization studies confirmed the ability of the vaccine to express the Pre-F protein and its superior immunogenicity compared to that of full-length F protein. These findings underscore the potential application of rAAV5 vector platforms in RSV vaccine development, and further investigation into their protective efficacy is warranted.